The impact of variation in reporting practices on the validity of recommended birdstrike risk assessment processes for aerodromes. (October 2016) - Allan, John; Baxter, Andrew; Callaby, Rebecca
Abstract: Birdstrikes are a major hazard to aviation; costing millions of pounds a year in damage and delays, as well as occasional hull losses and loss of life. The numbers and species of birds on and around airfields therefore need to be managed. To aid this process, airport staff often use risk assessments to identify which bird species cause the greatest risk and use the outcome to target their bird control effort. To this end, a number of national and international regulators, airports and other organisations recommend, or use, a derivation of a risk assessment process first published in 2006. This was developed using the UK Civil Aviation Authority's birdstrike database, employing data collected between 1976 and 1996. The risk assessment process relies on using the proportion of reported strikes that cause damage to the aircraft as a proxy for the likely severity of the outcome of strike incidents, so any change in the relative level of reporting of damaging and non-damaging strikes may significantly bias the results. The implementation of mandatory birdstrike reporting by the UK CAA in 2004 led to a significant increase in the number of strikes reported. If this involved a disproportionate increase in the number of non-damaging compared to damaging incidents reported, it may have impacted on the accuracy of the risk assessment process. This paper examines how differential reporting of damaging and non-damaging strikes can impact on the risk assessment process. It shows that changes in reporting practices since the original risk assessment was developed have impacted on the apparent birdstrike risk at UK airports, giving a false impression of increasing risk over the period. It makes recommendations for how the process can be better adapted to cope with such changes in the future, and how it should be modified for use in countries with different reporting regimes to that in the UK. Highlights: Some birdstrike risk assessment tools use data from pre 2004 to calculate the proportion of reported damaging strikes with a bird species. Mandating of birdstrike reporting by the UK CAA in 2004 has resulted in a large increase in the number of birdstrikes reported. This means that the risk assessment has been over-estimating the birdstrike risk at UK airports since 2004 when mandatory reporting was adopted. The relationship between bird mass and the proportion of strikes causing damage is recalculated here and should be be implemented immediately.